Effectiveness of hypothermia in preventing testicular injury following testicular torsion and detorsion - Semerciöz, A; Özercan, IH; Baltaci, AK; Mogulkoç, R; Yilmaz, B; Kelestimur, H (Lippincott Williams & Wilkins, 1998)
We have investigated the preventive and curative effects of hypothermia on experimentally induced torsion and detorsion of torsion injuries in male Wistar rats. Experimental torsion (720 degrees) and detorsion of torsion were applied for 2 and 4 h. The control animals were sham-operated. For hypothermic treatment, the animals were held and the testes exposed to the previously prepared ice bath (4 degrees C) for 2-4 h. All experimental groups (except detorsion of torsion for 2 h group) had significantly less germinal epithelial cell layers than in control animals. The values from detorsion of torsion for 4 h group were significantly lower than those seen in the 4 h torsion group. In the torsioned and detorsioned rats, hypothermic treatment significantly preserved the germinal epithelium as compared to their respective experimental groups. We conclude that hypothermic treatment is of clinical significance in the acute torsion cases. Furthermore, exposure to hypothermia before detorsion of torsioned testes may prevent the reperfusion-related injuries. (C) 1998 Lippincott-Raven Publishers.
Keywords: testicular torsion; detorsion; hypothermia; germinal epithelial cell layers